MENSCH-MASCHINE-INTERAKTION IM LEXIKOGRAPHISCHEN PROZESS ZU LEXIKALISCHEN INFORMATIONSSYSTEMEN - Kouassi, Konan (Dictionaries and Society. Proceedings of the XX EURALEX International Congress, 2022)
Dictionaries of today and tomorrow are rather digital products than print dictionaries. From the user’s perspective, electronic dictionary applications and in particular „lexical information systems“, also referred to as „digital word information systems“ are coming to the fore alongside Google searches. Given the rapid developments in the area of the automated provision of lexicographic information, more precisely the automatic creation of online dictionaries, the new role of the lexicographer in the modern lexicographic process is questionable. This article addresses this issue.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Beispielangaben; computergenerierte Angabe; Funktion des Lexikographen; lexikalisches Informationssystem; redaktionell erstellte Angaben